Occurrence of white striping and wooden breast in broilers fed grower and finisher diets with increasing lysine levels - Cruz, R. F.A.; Vieira, S.L.; Kindlein, L.; Kipper, M.; Cemin, H.S.; Rauber, S.M. (Poultry science, 2017)
Two experiments were conducted to evaluate the prevalence and severity of white striping (WS) and wooden breast (WB) in breast fillets from broilers fed diets with increasing digestible Lysine (dLys) from 12 to 28 d (Exp. 1) and from 28 to 42 d (Exp. 2). Trials were sequentially conducted using one-d-old male, slow-feathering Cobb 500 × Cobb broilers, both with 6 treatments and 8 replicates. Increasing dLys levels were equally spaced from 0.77 to 1.17% in Exp. 1 and from 0.68 to 1.07% in Exp. 2. The lowest dLys diet was not supplemented with L-Lysine (L-Lys) in either one of the studies and all other essential amino acid (AA) met or exceeded current commercial recommendations such that their dietary concentrations did not limit broiler growth. Four birds per pen were randomly selected from each replication and processed at 35 and 42 d in Exp. 1 and Exp. 2, respectively. Deboned breast fillets (Pectoralis major) were submitted to a 3 subject panel evaluation to detect the presence of WS and WB, as well as to provide scores of WS (0-normal, 1-moderate, 2-severe) and WB (0-normal, 1-moderate light, 2-moderate, 3-severe). Increasing the level of dLys had a positive effect on BW, carcass, and breast weight, as well as breast yield. White striping and WB prevalences were 32.3 and 85.9% in Exp. 1 and 87.1 and 89.2% in Exp. 2. Birds fed diets not supplemented with L-Lys had the lowest average WS and WB scores (0.22 and 0.78 in Exp. 1 and 0.61 and 0.68 in Exp. 2). White striping and WB presented linear responses to performance variables in Exp. 1, whereas quadratic responses were observed for all variables in Exp. 2. In conclusion, increasing the level of dLys improved growth performance and carcass traits as well as induced the occurrence and severity of WS and WB lesions.